Apakah Masuk Akal untuk Berdoa: Kajian Filsafat Agama - Manggala Wiriya Tantra; Dida Wanti (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
Human anxiety about life leads to a prayer ritual for religious people. Praying is considered an effective way to realize dreams, but there is also an assumption that it is unreasonable. The purpose of this study is to present a perspective on prayer. The research methodology uses literature studies to support the achievement of research objectives. The results of the study are that prayer is not a shortcut to solving problems that require mastery of all relevant facts. Someone who prays only with the aim of using God to solve their own problems, means violating the basic principles of all social and moral relationships. Prayer has a great influence on humans psychologically, such as being able to calm, soothe and convince themselves of the life choices that have been decided to be lived. The essence of prayer is an extension of togetherness and community concern.